The Effect of Streptozotocin-induced Diabetes on Bone Tissue around Endosseous Implants after Osseointegration - Obata, Toshitake; Oda, Mitsutaka; Kohgo, Takao; Yamamoto, Satoru; Kawasaki, Takao; Yokoyama, Atsuro; Iizuka, Tadashi (Japanese Journal of Oral Biology, 2002)
The purpose of this study was to investigate the effects of streptozotocin-induced diabetes on bone tissue around osseointegrated implants. Titanium implants were inserted in the femora of Wistar rats. At 8 weeks after implantation, diabetes was induced by intraperitoneal injection of streptozotocin (diabetic group). Age-matched rats served as a control group. Rats were sacrificed at 4 weeks after injection of streptozotocin. Histopathological and histomorphometric evaluations were carried out. The amount of newly formed bone in the control group was greater than that of the diabetic group. There was a difference in the ratio of bone-implant contact between the diabetic group and control group.